Prosthodontics at a Glance - Ram, S. M Sabita M (Jaypee Brothers Medical Publishers, 2018)
The aim of this book is to focus on Prosthodontics at a Glance. Prosthodontics is the dental specialty primarily concerned with the restoration and replacement of lost or damaged teeth. Prosthodontists are highly trained specialists with a unique understanding of all the elements that go into a beautiful, functional and natural-looking smile-not just the teeth, but also the gums, lips, and facial features. The subject of prosthodontics is being so vast that reading, remembering, comprehending and reproducing are seemed not easy. This book consists of four chapters, which include how to face viva voce, complete dentures, removable partial dentures, and fixed partial dentures. This book has been written with the aim to help students recap their knowledge on the subject. Reading of the book will enable the students to confidently face the exam and answer the viva voce. It can be carried daily to the clinic for reference during chairside viva. It is a book which every student should possess as it will give answers to most of the question asked in prosthodontics.